PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PT. FSG) - I Nyoman Tri Armawan (Universitas Mercu Buana, 2014)
Abstract: The purpose of this research is to test and analyze the influence oftransformational leadership style and work motivation on employees performance (study on PT.FSG). The sample used in this research consists of 86 respondents from 109 population. The method of sampling used is by simple random sampling, method dataanalysis used are multiple linear regression analysis.The result of the reseacrh using t test that transformational leadership style and workmotivation have positive significant influence to employees performance.Theresult of the research simultantly using F test, shows that all of the independentvariables influence significant to employees performance.Keywords: leadership style, work motivation, employees performance